Eddy current–nulled convex optimized diffusion encoding (EN‐CODE) for distortion‐free diffusion tensor imaging with short echo times. Issue 2 (25th April 2017) - Aliotta, Eric; Moulin, Kévin; Ennis, Daniel B.
Abstract : Purpose: To design and evaluate eddy current–nulled convex optimized diffusion encoding (EN‐CODE) gradient waveforms for efficient diffusion tensor imaging (DTI) that is free of eddy current–induced image distortions. Methods: The EN‐CODE framework was used to generate diffusion‐encoding waveforms that are eddy current–compensated. The EN‐CODE DTI waveform was compared with the existing eddy current–nulled twice refocused spin echo (TRSE) sequence as well as monopolar (MONO) and non–eddy current–compensated CODE in terms of echo time (TE) and image distortions. Comparisons were made in simulations, phantom experiments, and neuro imaging in 10 healthy volunteers. Results: The EN‐CODE sequence achieved eddy current compensation with a significantly shorter TE than TRSE (78 versus 96 ms) and a slightly shorter TE than MONO (78 versus 80 ms). Intravoxel signal variance was lower in phantoms with EN‐CODE than with MONO (13.6 ± 11.6 versus 37.4 ± 25.8) and not different from TRSE (15.1 ± 11.6), indicating good robustness to eddy current–induced image distortions. Mean fractional anisotropy values in brain edges were also significantly lower with EN‐CODE than with MONO (0.16 ± 0.01 versus 0.24 ± 0.02, P  < 1 x 10 ‐5 ) and not different from TRSE (0.16 ± 0.01 versus 0.16 ± 0.01, P  = nonsignificant). Conclusions: The EN‐CODE sequence eliminated eddy current–induced image distortions in DTI with a TE comparable to MONO and substantially shorter than TRSE. Magn Reson Med 79:663–672, 2018. © 2017 International Society for Magnetic Resonance in Medicine.